Mongolia Economic Update, April 2013 - Shiilegmaa, Altantsetseg; Gombosuren, Khandtsooj; Smith, Gregory (World Bank Group, Mongolia, 2014)
In 2012, Mongolia's economy continued to experience a high growth rate of 12.3 percent. This growth rate was however lower than anticipated as Mongolia saw its coal exports drop significantly due to China's economic slowdown. Most noticeably, Mongolia had to finance a large fiscal deficit of 8.4 percent of gross domestic product (GDP), a record in the last 13 years. It is concerning that similar fiscal trends might continue in 2013 with the economy growing at a double-digit rate but also accumulating another large fiscal deficit. As Mongolia embarks on its largest infrastructure investments ever which can be in part financed through a first successful sovereign Chinggis bonds issuance- greater attention has to be paid: (i) to preparing those investments rigorously to ensure maximum socioeconomic return and avoid potential wastage of public resources; and (ii) to reflecting their financing transparently in the national budget.